An assessment of the genetic toxicology of novel boron‐containing therapeutic agents. (26th April 2013) - Ciaravino, Vic; Plattner, Jacob; Chanda, Sanjay
<x xml:space="preserve">Abstract</x> Boron‐containing compounds are being studied as potential therapeutic agents. As part of the safety assessment of these therapeutic agents, a battery of genetic toxicology studies was conducted. The battery included a bacterial reverse mutation (Ames) assay, an in vitro chromosome aberration assay in peripheral human lymphocytes, and an in vivo rat micronucleus study. The following compounds represent some of the boron‐containing compounds that have been advanced to human clinical trials in various therapeutic areas. The borinic picolinate, AN0128, is an antibacterial compound with anti‐inflammatory activity that has been studied in clinical trials for acne and the treatment of mild to moderate atopic dermatitis. AN2690 (tavaborole) is a benzoxaborole in Phase 3 clinical trials for the topical treatment of onychomycosis, a fungal infection of the toenails and fingernails. Another benzoxaborole derivative, AN2728, a phosphodiesterase‐4 (PDE4) inhibitor, is in Phase 2 clinical trials for the treatment of atopic dermatitis. AN2898, also a PDE4 inhibitor, has been studied in clinical trials for atopic dermatitis and psoriasis. AN3365 is a leucyl‐tRNA synthetase inhibitor that has been in clinical development for the treatment of various Gram‐negative bacterial infections. These five representative compounds were negative in the three genotoxicity assays. Furthermore, AN2690 has been studied in mouse and rat 2‐year bioassays and was not found to have any carcinogenic potential. These results demonstrate that it is possible to design boron‐based therapeutic agents with no genetic toxicology liabilities. Environ. Mol. Mutagen. 54:338–346, 2013. © 2013 Wiley Periodicals, Inc.